2021
DOI: 10.1016/j.jcf.2020.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted local innervation results in less VIP expression in CF mice tissues

Abstract: Vasoactive Intestinal Peptide (VIP) is the major physiological agonist of the Cystic Fibrosis Transmembrane conductance Regulator (CFTR) chloride channel activity. VIP functions as a neuromodulator and neurotransmitter secreted by neurons innervating all exocrine glands. VIP is also a potent vasodilator and bronchodilator that regulates exocrine gland secretions, contributing to local innate defense by stimulating the movement of water and chloride transport across intestinal and tracheobronchial epithelia. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…Our most recent study in the C57Bl/6 homozygous Cftr tm1Kth F508del CF mice, the same model used in this paper, showed that VIP content is significantly reduced in the lungs, duodenum and sweat glands of young CF mice with minimal disease progression. In addition, we found that these mice present a highly discontinuous or sparse VIPergic network in the small intestine and that this VIPergic deficiency was not attributable to disease progression but to a disruption of the intrinsic innervation network [33] .…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…Our most recent study in the C57Bl/6 homozygous Cftr tm1Kth F508del CF mice, the same model used in this paper, showed that VIP content is significantly reduced in the lungs, duodenum and sweat glands of young CF mice with minimal disease progression. In addition, we found that these mice present a highly discontinuous or sparse VIPergic network in the small intestine and that this VIPergic deficiency was not attributable to disease progression but to a disruption of the intrinsic innervation network [33] .…”
Section: Discussionmentioning
confidence: 76%
“…Given that VIP is a neuropeptide with pleiotropic abilities, we decided to examine the distribution and abundance of VIP in the pancreas of male C57Bl/6 mice homozygous for the most common mutation in CF, F508del, and evaluate whether changes in VIP would correlate with changes in insulin and glucagon secretion that could contribute to the development of CFRD. We have measured the amount of VIP in both young (8-week-old) and older (17-week-old) CF mice, which reflect very early and late CF disease progression, respectively [33] . Our results show that VIP abundance and localization, semi-quantified by IHC and ELISA, were significantly reduced (~51% reduction) in the pancreas of CF mice at both 8 and 17 weeks of age.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations